Rapid Confirmation of the Zaire Ebola Virus in the Outbreak of the Equateur Province in the Democratic Republic of Congo: Implications for Public Health Interventions. (29th June 2018) - Mbala-Kingebeni, Placide; Villabona-Arenas, Christian-Julian; Vidal, Nicole; Likofata, Jacques; Nsio-Mbeta, Justus; Makiala-Mandanda, Sheila; Mukadi, Daniel; Mukadi, Patrick; Kumakamba, Charles; Djokolo, Bathe; Ayouba, Ahidjo; Delaporte, Eric; et al.
Abstract: Ten days after the declaration of the Ebola outbreak in the Democratic Republic of Congo, rapid identification of the species Zaire Ebola virus using partial gene amplification and nanopore sequencing backed up the use of the recombinant vesicular stomatitis virus–Zaire Ebola virus vaccine in the recommended ring vaccination strategy.